Phát triển năng lực số cho giảng viên đại học trong bối cảnh chuyển đổi số: nghiên cứu trường hợp tại Trường Đại học Hải Dương - Nguyễn Thị Thu Hà, Nguyễn Thị Thu Hà; Nguyễn Thị Hương, Nguyễn Thị Hương (Tạp chí Giáo dục, 2025)
Digital transformation has impacted accounting processes and methods, as well as changed the way accounting is studied, approached, and practiced in reality. This necessitates a transformation in accounting education and training to meet the demands of the integration era. Digital competence is not only a tool for lecturers to develop their own competences but also enables them to interact effectively with students, creating a dynamic and innovative learning environment. This article outlines the necessary digital competency framework for accounting lecturers, assesses the current state of digital competency among accounting lecturers at Hai Duong University, and proposes solutions to enhance digital competency. The goal is to train accounting graduates with strong expertise, professional skills, and the ability to master modern science and technology in the context of digital transformation. These measures aim to comprehensively develop digital competence for accounting lecturers in the era of digital transformation.